Geometric interpretation of Timelike mannheim curves by using riccati equations in minkowski 3-Space E3 1 - Yüzbaş, Zühal Küçükarslan; Bektaş, Mehmet (American Scientific Publishers, 2016)
In this paper, we consider the Riccati equations of the timelike Mannheim curves in Minkowski 3-space E31. We obtain the new results for this type curves and also give some geometric interpretation of the Riccati equations. © Copyright 2016 American Scientific Publishers All rights reserved.
Keywords: Mannheim curves; Minkowski space; Riccati equations; Timelike curves